The Problematic Use of Open-Ended Approach in Mathematics Learning in Elementary School - Ainul Mardiyah; Jamaris Jamaris; Sufyarma Marsidin; Yalvema Miaz; Yanti Fitria (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study is motivated by the emergence of problems experienced by teachers in using the open-ended approach in learning mathematics in elementary schools. This study aims to describe the obstacles faced by teachers in implementing mathematics learning using an open-ended approach in class, as well as provide solutions that can be done as an effort to overcome the obstacles encountered. This research used descriptive qualitative method. The data analysis technique used is the Miles and Huberman data analysis technique which goes through data reduction, data presentation, and verification. This research was conducted at SDN 13 Parit Putus, Ampek Angkek District, Agam Regency. The results showed the problems experienced by teachers in using the open-ended approach in learning mathematics in elementary schools